Current Management of Hepatic Encephalopathy: A Review Article - Ghosh , Jhumur; Ghosh, Jaya (Journal for Research in Applied Sciences and Biotechnology, 2023)
Hepatic encephalopathy, a neuropsychiatric syndrome stemming from liver failure, manifests in acute and chronic cases. The prevailing cause behind its development involves the neurotoxicity resulting from elevated ammonia levels in the brain, which can occur due to increased ammonia production or impaired ammonia excretion. The main objective in treating hepatic encephalopathy is to decrease ammonia levels. The detoxification of ammonia in this condition is regulated by two enzymes: glutaminase and glutamine synthetase. Numerous drugs, such as lactulose, rifaximin, BCAA, LOLA, glycerol phenylbutyrate, and zinc, have been utilized to treat hepatic encephalopathy. In terms of future research, experimental treatment options like fecal microbiota transplant, probiotics, bromocriptine, minocycline, indomethacin, ibuprofen, and flumazenil warrant investigation. Furthermore, albumin infusions have been shown to enhance cognitive function and improve the psychosocial quality of life, possibly by alleviating endothelial dysfunction in patients with minimal hepatic encephalopathy or previous episodes of hepatic encephalopathy. This review article offers a comprehensive overview of the current management strategies for hepatic encephalopathy.